The Influence of 'Ome TV': Exploring the Impact on Students' Listening Skills through Video Live Streaming - Ratnawati, Ratnawati; Rosmiaty, Rosmiaty; Angraeni, Lusy; Fikri, Andi Muhammad; Yuriatson, Yuriatson (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
This quantitative research study investigates the influence of the video live streaming application 'Ome TV' on students' listening skills. Undergraduate students from a vocational university in Makassar, Indonesia participated in the study, which utilized an online questionnaire to collect data on participants' listening abilities and their experiences with 'Ome TV'. The study aims to investigate the influence of 'Ome TV' on students' listening skills, identify challenges faced by students in using the application for listening practice, understand students' perceptions of the application's effectiveness, and provide recommendations for optimizing the integration of video live streaming applications in language learning environments. The findings reveal that most students perceived an improvement in their listening skills through 'Ome TV'; however, difficulties such as infrequent usage, limited improvement in understanding words with similar sounds, security concerns, and network quality issues were reported. The study concludes with practical recommendations for educators, curriculum designers, and developers to enhance the use of video live streaming applications in language learning settings. These findings contribute to the understanding of the potential benefits and challenges associated with video live streaming applications for improving students' listening proficiency.